Attitudes towards plagiarism among academics of the faculty of Medicine of Tunis. (16th November 2020) - Bettaieb, Jihène; Cherif, Ines; kharroubi, Ghassen; Mrabet, Ali
ABSTRACT: Assessing the extent of plagiarism within academics remains the first step in the fight against this behavior. The current study aimed to explore the attitudes of the Faculty of Medicine of Tunis (FMT)'s academics toward plagiarism. A cross-sectional study was conducted within the FMT during the 2018–2019 academic year. Data were collected using a questionnaire including the English version of the attitudes toward plagiarism questionnaire (ATPQ) which is composed of 29 statements divided into three attitudinal factors: positive, negative attitudes and subjective norms toward plagiarism. A total of 340 faculty members responded to the survey. The mean scores for both positive attitudes (28.8 ± 6.9) and subjective norms (24.6 ± 4.9) were between low to moderate and that of negative attitudes was moderate (22.4 ± 2.6). In multivariate analysis, participants with higher academic rank, those who had a good level of English or who attended English courses and those who attended workshops in scientific writing were less tolerant toward plagiarism. The implementation of courses on research practices as well as the introduction of medical English courses in the FMT's post graduate program could constitute relevant approaches to limit the extent of plagiarism.